Strategies for restructuring the Agricultural Research Council of Nigeria: Process, opportunities, and lessons - Babu, Suresh Chandra; Oyedipe, E. O.; Ajakaiye, Olusanya; Ajoni, K. (International Food Policy Research Institute, 2017)
This paper aims to develop specific strategies for reforming the Agricultural Research Council of Nigeria (ARCN) for achieving greater efficiency, effectiveness, impact, and sustainability through its constituent institutions. Based on a two-year consultative and interactive process of internal discussion, external learning, and analysis of various restructuring options, this paper proposes specific interventions for promoting results-based approaches to priority setting, resource mobilization and allocation, effective implementation of research programs, enhanced and timely delivery of results, mon-itoring and evaluation, impact assessment, and improved networking among domestic and international partners. The paper recommends a phased approach to ARCN reforms, beginning with organizational transformation and capacity strengthening at all levels. In addition, issues, challenges, and opportunities for sustainable funding, integration of re-search, extension, education, and the regulatory mandates of ARCN are discussed. Finally, an implementation plan for restructuring ARCN is presented.